Canadian Labour Relations Under the Charter: Exploring the Implications - Carter, Donald (Relations industrielles / Industrial Relations, 1988)
Can legal tools used by judges and lawyers adequately deal with the public policy issues that underly any alteration of our present system of industrial relations.